A novel intelligent system to nitrogen content prediction in plants using indirect chlorophyll measurements - Ulson, Jose Alfredo Covolan [UNESP]; Boas, RLV; Godoy, LJG; de Souza, A. N. (Amer Soc Agr Engineers, 2001)
The accurate identification of the nitrogen content in plants is extremely important since it involves economic aspects and environmental impacts, Several experimental tests have been carried out to obtain characteristics and parameters associated with the health of plants and its growing. The nitrogen content identification in plants involves a lot of non-linear parameters and complexes mathematical models. This paper describes a novel approach for identification of nitrogen content thought SPAD index using artificial neural networks (ANN). The network acts as identifier of relationships among, crop varieties, fertilizer treatments, type of leaf and nitrogen content in the plants (target). So, nitrogen content can be generalized and estimated and from an input parameter set. This approach can form the basis for development of an accurate real time system to predict nitrogen content in plants.
Keywords: Intelligent Systems; neural nets; SPAD index